Metal source of gold deposits in the Jiaoxibei area, Eastern China: Insights from trace element analysis of gold and pyrite. Issue 1 (29th September 2021) - Lu, Jilong; Fan, Yuchao; Yin, Yechang; Xiong, Yuxin; Guo, Jinke; Tian, Wu; Zhao, Xinyun
Abstract: The metal source of gold deposits in the Jiaoxibei area, eastern China, has been investigated by many researchers, but no consensus has been reached so far. In this study, three typical gold deposits, the Xinli, Jiaojia, and Dayingezhuang deposits, were selected for trace element analysis of gold and pyrite to constrain the metal source. Pyrite from these three deposits has similar morphological and compositional characteristics, and can be divided into three types: Py1 with euhedral to subhedral textures, Py2 with subhedral to anhedral textures with micro‐fractures, and Py3 with subhedral to anhedral textures and intergrowing polymetallic sulfides. Among them, Py2 and Py3 were formed in the main ore‐forming stage and they are the dominant host minerals of visible gold. In these deposits, visible gold occurs mainly in micro‐fractures or as inclusions in Py2 and Py3. Most of the pyrite has extremely low concentration of invisible gold, indicating that visible gold in the Jiaoxibei district is not a product of the remobilization of invisible gold from earlier pyrite. Both Py2 and Py3 are characterized by low Co concentration of <100 ppm and Co/Ni ratio of <1, which are similar to those of pyrite in sedimentary rocks. Therefore, ore‐forming metals of these gold deposits in the Jiaoxibei district may originate mainly from a sediment‐related metal source. Abstract : In‐situ analyses of ore minerals from gold deposits in the Jiaoxibei district indicate that ore‐forming metals of gold deposits in the Jiaoxibei district may originate mainly from a sediment‐related metal source.